Pengaruh Penundaan Penanganan Spesimen Sputum Selama 24 Jam terhadap Hasil Pemeriksaan Basil Tahan Asam (BTA) di Puskesmas Langgam - Ramadhani, Febi; Shory, Shofyyan (JURNAL RISET INOVASI DAERAH, 2023)
Tuberculosis (TB) is still a big problem for the Indonesian government as well as for the Pelalwan Regency Government, especially Langgam sub-district. In Langgam District, the distance between the patient's residence and the community health center can be up to 4 hours or more, due to the distance and number of laboratory personnel, samples cannot be examined immediately, resulting in delays in sample examination. The aim of this research was to determine the effect of delaying handling of sputum specimens for 24 hours on the results of acid-fast bacilli (BTA) examination readings at the Langgam Community Health Center. The research design carried out was an analytical research design with a cross sectional type. This research was conducted in July 2022 - February 2023 at the Langgam Community Health Center using 40 samples. The results show the effect of delaying handling of sputum specimens for 24 hours on the reading results of acid-fast bacilli (BTA) examinations at the Langgam Community Health Center.